Dynamic Analysis of Antibiotic Resistance of Escherichia coli and Staphylococcus aureus Strains in Patients with Urinary Tract Infections in a Specialized Psychiatric Hospital - N. N. Mitrofanova; I. A. Sorokin (Антибиотики и Химиотерапия, 2024)
Urinary tract infection (UTI) is one of the most common infections acquired in psychiatric hospitals. The aim of this study was to analyze the change in antibiotic activity against Escherichia coli and Staphylococcus aureus and their concentrations in patients at a specialized psychiatric hospital, which is necessary for the dynamic analysis of antibiotic resistance and to prevent its future development. The authors retrospectively analyzed 144 outcomes (34 men and 110 women) with an identiﬁed UTI, the causative pathogens of which were E. coli (N=82) and a representative of the gram-positive ﬂora, S. aureus (N=62). The results suggest that antibiotic resistance of UTI pathogens may have a negative trend on the prevalence of resistant strains. Ciproﬂoxacin was the most active antibiotic against UTIs caused by E. coli. S. aureus is more resistant to antibiotics and has a greater predisposition to ﬁxation in the urinary tract due to the creation of bioﬁlms.